(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: This study was performed to probe the antimicrobial resistance and virulence genes profiling in Pseudomonas aeruginosa recovered from the cases of pericarditis in broiler chickens. Materials and Methods: The samples (n = 250) collected from the cases of pericarditis in broiler chickens were bacteriologically examined. Antimicrobial susceptibility was tested by disc diffusion technique. The isolates were genotypically studied for the presence of antimicrobial resistance and virulence gene traits. Finally, the nucleotide sequence of representative resistance gene (mexR gene) and virulence genes (toxA and lasI genes) was analyzed. Results: P. aeruginosa was isolated from 45 samples (18%). Antimicrobial susceptibility testing revealed multidrug resistance in most of the recovered P. aeruginosa isolates, whereas colistin and imipenem were the furthermost in vitro-sensitive antibiotics. Antimicrobial resistance genes, such as blaCTX, fox, and mexR, were prevalent in 100%, 80%, and 100% of the isolates, respectively. PCR confirmed virulence genes such as toxA, exoY, lasB, and lasI in 100%, 60%, 80%, and 80% of the isolates, respectively. Nucleotide sequence analysis of representative resistance gene (mexR gene) and virulence genes (toxA and lasI genes) revealed a high correlation between P. aeruginosa recovered from pericarditis in broiler chickens in the present study with PAO1 (reference strain) and with other sequences published on the GenBank representing different localities worldwide. Conclusion: It could be concluded that P. aeruginosa recovered from pericarditis in broiler chickens in the current study is highly virulent bacteria, resisting most of the therapeutic agents which not only bear hazards for poultry industry but also represent a public health concern. J. Adv. Vet. Anim. Res., 7(3): 452-463, Sep 2020 http://doi.org/10.5455/javar.2020.g441